2016
DOI: 10.1016/j.jviscsurg.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative ileus: Pathophysiology, incidence, and prevention

Abstract: Postoperative ileus (POI) is a major focus of concern for surgeons because it increases duration of hospitalization, cost of care, and postoperative morbidity. The definition of POI is relatively consensual albeit with a variable definition of interval to resolution ranging from 2 to 7 days for different authors. This variation, however, leads to non-reproducibility of studies and difficulties in interpreting the results. Certain risk factors for POI, such as male gender, advanced age and major blood loss, hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
201
2
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(257 citation statements)
references
References 79 publications
9
201
2
15
Order By: Relevance
“…Risk factors for postoperative bowel obstruction were associated with male gender, advanced age, significant blood loss, the surgical approach used, intro-abdominal infection, anastomotic leak, emergency surgery, and opioid administration. [44] In 1 study, the investigators highlighted opioids’ role in aggravating the risk for postoperative bowel obstruction. [45] Our meta-analysis demonstrated that operative time was visibility longer for RTME than LTME, suggesting that patients were administered more anesthetics, especially opioids.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for postoperative bowel obstruction were associated with male gender, advanced age, significant blood loss, the surgical approach used, intro-abdominal infection, anastomotic leak, emergency surgery, and opioid administration. [44] In 1 study, the investigators highlighted opioids’ role in aggravating the risk for postoperative bowel obstruction. [45] Our meta-analysis demonstrated that operative time was visibility longer for RTME than LTME, suggesting that patients were administered more anesthetics, especially opioids.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the reported incidence of human POI ranges from 2% to 60% depending on the POI or PPOI descriptors applied in the study [2,19]. The criteria used for classification vary greatly, which probably contributes to the disparity in certain study-derived data.…”
Section: General and Humanmentioning
confidence: 99%
“…The criteria used for classification vary greatly, which probably contributes to the disparity in certain study-derived data. For example, the reported incidence of human POI ranges from 2% to 60% depending on the POI or PPOI descriptors applied in the study [2,19]. Efforts to establish more specific criteria for each of these POI subcategories [2] might facilitate comparisons between individual studies.…”
Section: General and Humanmentioning
confidence: 99%
“…Intestinal manipulation can stimulate innate immune cells and lead to an inflammatory response, altering the immune system and subsequently our inflammatory status in POI . Previous studies have pointed to an adipose local immune response after intestinal manipulation as the main cause of inflammation in POI . Intestinal inflammation is associated with increased myeloperoxidase (MPO) enzyme activity in the intestines.…”
Section: Introductionmentioning
confidence: 99%